2016
DOI: 10.21037/jtd.2016.05.94
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility and tendency of the soluble receptor for advanced glycation end products (sRAGE) in exudative pleural effusion

Abstract: Background:The soluble receptor for advanced glycation end products (sRAGE) may have an inflammatory or homeostatic function in lung tissue. The aim of this study was to assess the usefulness of sRAGE as a diagnostic marker for exudative pleural effusions, which are common manifestations of a variety of diseases. Methods:Patients with an undiagnosed pleural effusion were prospectively enrolled between January 2013and January 2015. Samples of blood and pleural fluid were centrifuged and the supernatant stored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The present study demonstrated that there was no signi cant difference among CHB patients with different viral loads, which was con rmed in the three subgroups with high viral loads HBeAg(-) IR phase, HBeAg(+) IT phase and HBeAg(+) IA phase. These ndings indicate that sRAGE may not be a factor of the host innate defense system that participates in HBV replication, consistent with a previous report showing that serum sRAGE levels were linked to the chronic in ammation in lung disease rather than pathogen infection [24].…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that there was no signi cant difference among CHB patients with different viral loads, which was con rmed in the three subgroups with high viral loads HBeAg(-) IR phase, HBeAg(+) IT phase and HBeAg(+) IA phase. These ndings indicate that sRAGE may not be a factor of the host innate defense system that participates in HBV replication, consistent with a previous report showing that serum sRAGE levels were linked to the chronic in ammation in lung disease rather than pathogen infection [24].…”
Section: Discussionsupporting
confidence: 92%
“… 10 12 13 28 A previous study reported lower levels of pleural fluid sRAGE in patients with bacterial pneumonia compared with those with tuberculosis or lung cancer. 29 We only observed a trend of higher levels of pleural fluid sRAGE with lupus pleuritis when compared with malignant pleural effusion.…”
Section: Discussionmentioning
confidence: 57%
“…10 12 13 28 A previous study reported lower levels of pleural fluid sRAGE in patients with bacterial pneumonia compared with those with tuberculosis or lung cancer. 29 We only observed a trend of higher levels of pleural fluid ADA catalyses the deamination of adenosine, which is a crucial suppressor of the inflammation. 30 Moreover, Lupus Science & Medicine ADA is involved in the differentiation and maturation of the immune cells such as lymphocytes.…”
Section: Discussionmentioning
confidence: 71%
“…The RAGE pathway has been reported in the pathogenesis of lung diseases such as chronic obstructive pulmonary disease (COPD), interstitial lung diseases, and ARDS (9,10). In recent years, the therapeutic intervention of the RAGE pathway has been demonstrated to benefit patients suffering from ARDS, COPD, pulmonary fibrosis, and other pathologies associated with the pulmonary system (11)(12)(13)(14)(15). Notably, enhanced levels of RAGE ligands are associated with inflammatory disorders Fields (16)(17)(18), such as diabetes or other chronic inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%